EFFECTS OF SALT STRESS ON ECOPHYSIOLOGICAL TRAITS OF WHEAT - Kholliev Askar Ergashovich; Mashkhura Yandashova (Web of Journals Publishing, 2024)
The article presents the data obtained in the study of the characteristics of the effect of soil salinity on the transpiration rate of wheat varieties. The rate of transpiration was determined at the tuber, flowering and milk-ripening stages of the cultivars. Based on the given results, it was noted that the value of the above indicator varies to different degrees in the section of varieties, depending on the soil salinity and the biological and variety characteristics of the varieties.
Keywords: winter wheat varieties, salinity, transpiration, water exchange, salt tolerance.